Beneficial effect of compound essential oil inhalation on central fatigue - Chenxia Han; Feng Li; Simin Tian; Yan Liu; Huai Xiao; Xiumei Wu; Weiyue Zhang; Wei Zhang; Meng Mao (BMC, 2018)
Abstract Backgrounds Although the physical and mental enhancement effect of essential oils have been proved, the beneficial effect of essential oil in central fatigue remains unclear. In this study, we extracted essential oils from nine aromatic plants to make a compound essential oil, and detected the therapeutic effect of central fatigue by daily aerial diffusion. Methods Thirty-three rats were randomly and equally divided into control group, chronic sleep deprivation group, and compound essential oil inhalation group. Central fatigue was generated by chronic sleep deprivation. Results After 21-day various interferences, it is found that the sleep deprivation rats showed an evident decrease in physical endurance, negative emotion, and cognitive dysfunction compared with the control group, and the group that treated with the compound essential oil behaved significantly better than central fatigue group. Conclusion We concluded that this formula of essential oils could alleviate central fatigue on rats, and our study provides a new direction of application of aromatic therapy, which could be expanded to insomnia, depression and other healthy issue in the further research.